STUDENT PERCEPTIONS IN THE APPLICATION OF HYBRID LEARNING WITH COGNITIVE ABILITY IN LEARNING INNOVATION COURSES - Fitria Wulandari (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to determine student perceptions in theimplementation of Hybrid learning and the relationship between hybrid learning and studentcognitive abilities in the Learning Innovation course. This type of research uses mixedmethods research methods. The designs in this study were sequential explonatorydesigns. The sampling technique used purposive sampling. The sample in this studywas the 3rd semester students of class A3 in the PGSD study program,Muhammadiyah University of Sidoarjo, totaling 40 students, consisting of 37 womenor 92.5% of the total and 3 men or 7.5% of the total. The instruments used in thisstudy were observation sheets, interview sheets, questionnaire sheets, studentcognitive ability test sheets. From the results of qualitative data shows that theperception of students in Hybrid learning is in the very high category, as many as12.5% ​​of students strongly agree, 72.5% of students agree with the implementation ofhybrid learning in courses. Meanwhile, based on the calculation of the results of asimple correlation (r) of 0.754, it has a positive and significant relationship betweenHybrid learning and students' cognitive abilities. Thus, it can be concluded that thebetter the student's perception of hybrid learning, the higher the cognitive ability ofstudents in the learning innovation course.